Pengaruh Motivasi, Mutasi dan Kualitas Pelayanan Publik Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Kupang - Medah, Mardiana Henderika; Man, Stanis; Taolin, Daniel; Niha, Simon Sia; Yasinto, Yulius (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the influence of motivation, transfer and quality of public services on employee performance through job satisfaction as an intervening variable at the Kupang Regency Population and Civil Registration Service. Data collection methods include observation, recording and questionnaires, using the SmartPLS application. The sample for this research used the census method, totaling 69 employees of the Kupang Regency Population and Civil Registration Service. The results of this research reveal that statistically the performance variable of Kupang Regency Dukcapil service employees is influenced by job satisfaction. The job satisfaction variable is not influenced by service quality, but is influenced by employee motivation and transfer variables. Employee performance variables are not influenced by mutations, but are influenced by service quality variables and motivation variables. The job satisfaction variable cannot act as a mediating variable between the service quality variable and employee performance. Furthermore, the job satisfaction variable can mediate the influence of motivation and mutation variables on employee performance in the Kupang Regency Dukcapil service.